Variation in lower limb power and three point shot performance following repeated sprints: one vs. five changes of direction in male basketball players - Brini, S.; Delextrat, A.; Bouassida, A. (Journal of Human Kinetics, 2021)
Repeated sprint ability (RSA) with five changes of direction was well admitted to replicate real basketball game situations, but the additional changes of direction may affect some fundamental skills and performances in basketball. The aim of this study was to investigate the effects of RSA with one vs. five changes of direction (IRSA5COD) on squat jump (SJ), five jump test (FJT) and three point shot (3PS) performances in male basketball players. Sixteen participants (23.4 ± 2.3 years; 1.86 ± 0.10 m; 77.8 ± 7.7 kg) randomly performed eight testing sessions consisting of either RSA (10 repetitions of (15 m + 15 m)) or IRSA5COD (10 repetitions of (5 m + 5 m + 5 m + 5 m + 5 m + 5 m)) performed alone or immediately followed by the SJ, FJT or 3PS. The heart rate (HR) and ratings of perceived exertion (RPE) were continuously recorded, while blood lactate concentration was measured post-tests. Differences between RSA and IRSA5COD were evaluated by a Student t-test for paired samples, while analyses of variance (ANOVAs) with repeated measures assessed differences in SJ, FJT and 3PS performance between baseline, post-RSA and post-IRSA5COD. A significantly poorer FJT performance post-RSA was shown compared to baseline (7.47 ± 0.47 vs.7.54 ± 0.47 m, p = 0.01) and post-IRSA5COD (7.47 ± 0.47 vs. 7.56 ± 0.49%, p = 0.048). Significantly lower 3PS accuracy was also observed post-IRSA5COD compared to baseline (41.3 ± 3.1 vs.53.1 ± 2.8%, p = 0.003) and post-RSA (41.3 ± 3.1 vs. 48.1 ± 3.7%, p = 0.033). These results suggest that jump performance required for crucial actions such as lay-ups is negatively affected by longer sprints (15-m) with few changes of direction, while 3PS accuracy is impaired by shorter sprints with many changes of direction. These situations should be replicated when training these particular abilities to optimize training adaptations.